Study on proximal humerus evaluation of effective treatment (SPHEER) - what is the effect of rehabilitation compliance on clinical outcomes of proximal humerus fractures - Nah, Kenneth Ming Foo (2024)
Proximal humeral fractures (PHFs) are 3rd commonest fragility fractures and cause significant functional impairment. This paper sought to determine impact of rehabilitation compliance on the clinical outcomes for non-surgically managed PHFs, while ascertaining reasons for non-compliance which can be addressed to improve compliance.